Su Origene, Commento a Matteo 15, 10-19 - Simonetti, Manlio (Augustinianum, 2012)
This essay analyzes Origen's Commentary on Matthew, specifically the pericope of the 'rich young man', by comparing its ancient Latin translation to the Greek text as it stands in Klostermann's edition, taking into consideration, on the one hand, the surviving manuscripts and, on the other, the dissimilar Greek version used by the ancient translator. The paper illustrates how a painstaking research of the commentary's sources unexpectedly reveals Origen's exegesis and doctrines, which often remain hidden in modern translations of Origen's works.